ELECTROHYDRAULIC METHOD FOR PROCESSING OF THE PHOSPHORUS CONTAINING SLUDGES - Nussupbekov, B.R.; Sakipova, S.E.; Edris, A.; Khassenov, A.K.; Nussupbekov, U.B.; Bolatbekova, M. (KU Publ., 2022)
The creation of an effective method for processing toxic waste from phosphorus production, as well as the suppression of the sludge formation process itself, are still relevant. This article discusses a method for processing toxic phosphorus sludge using electro hydraulic impulses. The phosphorus sludge structures before and after treatment with electric discharges are shown. The histograms of the distribution of phosphorus sludge particles by size after processing with electrohydraulic pulses are considered. It's established the content of large droplets is low and on the contrary the high content of droplets of small size in the phosphorus sludge at the electro hydraulic treatment result.
Keywords: phosphorus; sludges; electro-hydraulic processing; structure; pulses number; dispersed composition; toxic waste